Effects of computerized nurse careplanning on selected health care effectiveness measures. - Keller, L. S. (American Medical Informatics Association, 1991)
A computerized nurse careplanning system (CNCP) was implemented on two nursing units of the Veterans' Affairs Medical Center, Washington, DC. This pretest, post-test experimental study sought to determine the effects of implementing this system on selected nursing care activities and associated patient outcomes. Effects on outcomes of job satisfaction, use of careplanning and competency of staff nurses were also examined. The sample consists of four medical nursing wards with registered nurses (n = 40) and patients (n = 160 as subjects). Data collection included nurse questionnaires, patient interviews and chart reviews. Results of the multiple regression analyses will be summarized here. Plans for further enhancement of CNCP will be discussed.